Outcomes of Microscopic Residual Tumor after Curative-Intent Surgery in Adenocarcinoma of Esophagogastric Junction - Chawisa Nampoolsuksan; Khajohnsak Bhocksombud; Thammawat Parakonthun; Tharathorn Suwatthanarak; Thikhamporn Tawantanakorn; Nicha Srisuworanan; Voraboot Taweerutchana; Atthaphorn Trakarnsanga; Chainarong Phalanusitthepha; Jirawat Swangsri; Thawatchai Akaraviputh; Asada Methasate; et al. (Siriraj Medical Journal)
Objective: Radical surgery is the mainstay treatment for adenocarcinoma of the esophagogastric junction. The presence of microscopic residual tumor tissue after curative-intent surgery is associated with recurrence. This study compared the outcomes of patients with microscopic residual tumor (Residual+ group) and those without microscopic residual tumor (Residual- group).